An Investigation of Physiological Arousal in Children with Autism and Co-morbid Challenging Behaviour - Lydon, Sinéad (Trinity College (Dublin, Ireland). School of Psychology, 2016)
Challenging behaviour is prevalent among individuals with autism spectrum disorders (ASD). While operant theory has allowed for the development of effective behavioural interventions for challenging behaviours such as self-injury and stereotypy, the aetiology of such behaviours remains largely unknown. An abundance of theories exist that posit that these behaviours may be the result of physiological dysregulation or atypical physiological processes. However, there is currently a limited body of research empirically examining the relationship between physiological activity and engagement in challenging behaviour. The purpose of the current program of research was to examine the contribution of psychophysiological measurement to our understanding and assessment of challenging behaviour in ASD.
Keywords: Autism; Ph.D. Trinity College Dublin; Psychology, Ph.D.